SINGLE EXPONENTIAL SMOOTHING IN FORECASTING TOOLS AND MEDICINE STOCKS - Revi Sesario; Tobias Duha; Agry Alfiah; Susatyo Adhi Pramono; Pandu Adi Cakranegara (INFOKUM, 2022)
Problems that arise when acquiring equipment and pharmaceuticals include procurement delays caused by waiting for genuine data from the storage area, as well as surplus stock of various types of drugs. This is due to the fact that administrative documents are still kept in the traditional manner. In this article, we provide forecasting tool and medicine stock based on the demand ratio in order to overcome stock delays and surplus stock. Because of the needs (in the month of forecasting carried out and the amount of data held), single exponential smoothing with alpha 0.1 is utilized. The prediction findings are also considered accurate because the forecasting smoothing computation with an average error value of MAD (21,4), MSE (710,4), and MAPE (7%) was assessed as very good.